Population genetic diversity of giant mottled eels (Anguilla marmorata) in Quang Tri - Nguyễn, Anh Tuấn; Võ, Đức Nghĩa; Trần, Thị Thúy Hằng; Đào, Tấn Học; Đặng, Thanh Long (Hue University Journal of Science: Natural Science, 2022)
This study was conducted to evaluate the population genetic diversity of the wild Anguilla marmorata in Quang Tri province by comparing the DNA sequences of the mitochondrial control region (CR) gene with those of other giant mottled eel populations in the world. The results indicate that the genetic distance between individuals in the Quang Tri population ranged from 0 to 0.261, with an average of 0.024. Among 31 individuals, there were 203 distinct polymorphism sites (S), which led to 209 mutation sites (Eta) and 31 different haplotypes. The average number of distinct nucleotides (k) was 29,299. The nucleotide diversity factor (Pi) accounted for 26.09 × 10–3, and the minimum number of recombination processes (Rm) in the population was 51 events. The majority of eel samples collected at the site had close genetic relationships with those of the North Pacific population (27/31 individuals), and four eel samples had close genetic relationships with those of the South Pacific population. The finding of the four giant mottled eels in Quang Tri belonging to the South Pacific population is considered a significant result of this study.